2017
DOI: 10.1542/peds.2017-1715
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Guideline to Decrease Use of Acid-Suppressing Medications in the NICU

Abstract: Implementation of an evidence-based guideline in our unit led to a significant decrease in nonindicated use of acid-suppressing medications and reduced the burden of exposure to PPIs/H2RAs. This intervention could feasibly be implemented in other similar inpatient settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…During the same period, recent alerts pointed to the association of PPIs with bone fractures, community-acquired pneumonia and bacterial diarrhoea [57] . Furthermore, the PPI efficiency for reflux symptoms is not demonstrated amongst infants [58] . This prompted the re-affirmation of clinical guidelines for the judicious and limited use of PPIs in paediatric patients [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 92%
“…During the same period, recent alerts pointed to the association of PPIs with bone fractures, community-acquired pneumonia and bacterial diarrhoea [57] . Furthermore, the PPI efficiency for reflux symptoms is not demonstrated amongst infants [58] . This prompted the re-affirmation of clinical guidelines for the judicious and limited use of PPIs in paediatric patients [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 92%
“…Medicines utilization research informs us on trends, on between unit variability and on the impact of guideline implementation. This utilization research is not limited to exposure to antibiotics [ 4 , 9 , 10 , 11 , 12 , 13 , 14 , 20 ], but has been illustrated using data on drugs for gastroesophageal reflux, analgesics or anti-epileptic drugs [ 4 , 17 , 18 , 19 , 20 , 21 ]. We hereby illustrate how a shift in practices can result in another irrational practice with another compound (shift from prokinetics to anti-acid drugs to treat reflux associated-apnea).…”
Section: Discussion: Perspectives To Further Improve Rational Use mentioning
confidence: 99%
“…Extensive variability in the use of analgesics is observed. For both ATC groups, research on implementation strategies proved to be effective [ 21 , 26 ]. For AEDs, we use the data on the minor shifts in drug utilization patterns to illustrate the relevance to develop tools for more accurate diagnosis, and guidelines to reduce the duration of exposure [ 27 ].…”
Section: Discussion: Perspectives To Further Improve Rational Use mentioning
confidence: 99%
See 1 more Smart Citation
“…By educating care providers and staff regarding appropriate evidence-based use of these medications, their use was reduced, although there was no concomitant decrease in potentially associated adverse events such as infection, fractures, or NEC. However, the authors reported NEC and fractures to be such rare events in their unit that a conclusion relating to these adverse outcomes with H2RA/PPI use could not be drawn [54].…”
Section: Gerd Treatmentsmentioning
confidence: 97%